Which personality traits are related to traditional bullying and cyberbullying? A study with the Big Five, Dark Triad and sadism. (1st February 2017) - van Geel, Mitch; Goemans, Anouk; Toprak, Fatih; Vedder, Paul
Abstract: Studies have shown that both Big Five and Dark Triad (Machiavellianism, narcissism, psychopathy) personality traits are related to traditional bullying and cyberbullying behaviors in adolescents as well as in adults. Increasingly, scholars call for sadism as an addition to the Dark Triad in the study of antisocial and delinquent behaviors. In the current study we analyze whether the Big Five, Dark Triad and sadism predict traditional bullying and cyberbullying. The sample consisted of 1568 participants (61.9% female), ranging in age from 16 to 21 years. Using hierarchical linear regression analyses, controlling for age and gender, it was found that agreeableness, Machiavellianism, psychopathy and sadism were significantly related to traditional bullying, and agreeableness and sadism were related to cyberbullying. Taken together, the results more firmly establish that sadism could be a predictor of antisocial behaviors, by establishing its relations with bullying and cyberbullying. Highlights: Agreeableness, Machiavellianism, and psychopathy predict traditional bullying. Agreeableness predicts cyberbullying. Sadism predicts traditional bullying when Dark Triad traits are controlled for. Sadism predicts cyberbullying when Dark Triad traits are controlled for.